Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b)23.75+25.23+180
23.(75+25)+180
23.100+180
2300+180
2480
c)
-257-(-257)+100
(-257+257)+100
0+100
100
d)
-3-4+6
-3+(-4)+6
-7+6
-1
a) 7x - 5 = 16 b) 156 - 2x = 82 c) 10x + 65 = 125
=> 7x = 16 + 5 => 2x = 156 - 82 => 10x = 125 - 65
=> 7x = 21 => 2x = 74 => 10x = 60
=> x = 21 : 7 => x = 74 : 2 => x = 60 : 10
=> x = 3 => x = 37 => x = 6
Vậy x = 3 Vậy x = 37 Vậy x = 6
d) 8x + 2x = 25.2 e) 15 + 5x = 40 f) 5x + 2x = 6 - 5
=> 10x = 50 => 5x = 40 - 15 => 7x = 1
=> x = 50 : 10 => 5x = 25 => x = 1 : 7
=> x = 5 => x = 25 : 5 => x = 1/7
Vậy x = 5 => x = 5 Vậy x = 1/7
Vậy x = 5
g) 5x + x = 150 : 2 + 3 h) 6x + 3x = 5 : 5 + 3 i) 5x + 3x = 3 : 3 . 4 + 12
=> 6x = 75 + 3 => 9x = 1 + 3 => 8x = 1 . 4 + 12
=> 6x = 78 => 9x = 4 => 8x = 4 + 12
=> x = 78 : 6 => x = 4 : 9 => 8x = 16
=> x = 13 => x = 4/9 => x = 16 : 8
Vậy x = 13 Vậy x = 4/9 => x = 2
Vậy x = 2
j) 4x + 2x = 68 - 2 : 2 k) 5x + x = 39 - 3 : 3 l) 7x - x = 5 : 5 + 3 . 2 - 7
=> 6x = 68 - 1 => 6x = 39 - 1 => 6x = 1 + 6 - 7
=> 6x = 67 => 6x = 38 => 6x = 7 - 7
=> x = 67 : 6 => x = 38 : 6 => 6x = 0
=> x = 67/6 => x = 19/3 => x = 0
Vậy x = 67/6 Vậy x = 19/3 Vậy x = 0
m) 7x - 2x = 6 : 6 + 44 : 11
=> 5x = 1 + 4
=> 5x = 5
=> x = 5 : 5
=> x = 1
Vậy x = 1
Mỏi tay ~~~~~~~~~~~~~~
a)3x - 105 : 21 = 19
3x - 5 = 19
3x = 19 + 5
3x = 24
x = 24 : 8
x = 3
b, x - 7 = 14 - 3 . 23
x - 7 = 14 - 3 . 8
x - 7 = 14 - 24
x - 7 = -10
x = (-10) + 7
x = -3
HT và $$$
Bài 2:
a) 3x - 105 : 21= 19 b) x - 7= 14 - 3 . 2^3
3x - 5 = 19 x - 7= 14 - 3.8
3x = 19+ 5 x - 7= 14 - 24
3x = 24 x - 7= -10
x = 24 : 3 x = -10+7
x = 8 x = -3
3\(x\) - 42 = 3.23
3\(x\) - 42 = 3.8
3\(x\) - 42 = 24
3\(x\) = 24 + 42
3\(x\) = 66
\(x\) = 66: 3
\(x\) = 22
3x - 42 = 3 . 23
3x - 42 = 3 . 8
3x - 42 = 24
3x = 24 + 42
3x = 66
x = 66 : 3
=> x = 22.
(3x + 1) . 33 - 1040 = 53 . 2 + 21
(3x + 1) . 33 - 1 = 271
(3x + 1) . 33 = 271 - 1
(3x + 1) . 33 = 270
(3x + 1) . 27 = 270
(3x + 1) = 270 : 27
(3x + 1) = 10
3x = 10 - 1
3x = 9
x = 9 : 3
x = 3
\(\Rightarrow\)x = 3
học tốt
156: (3\(x\) - 2) = 3.22
3\(x\) - 2 = 156 : 3.22
3\(x\) - 2 = 13
3\(x\) = 13 + 2
3\(x\) = 15
\(x\) = 15 : 3
\(x\) = 5